Trajetória de adoecimento da pessoa com doença renal crônica em tratamento hemodialítico - Pâmela Malheiro Oliveira (2021)
Chronic Kidney Disease (CKD) is a progressive disease characterized by the presence of kidney damage and irreversible and gradual loss of glomerular filtration rate. Patients on hemodialysis live in particular conditions, need to have access to health services, need to strictly control their diet and fluid consumption, have restricted work activities, in addition to having reduced physical activity and loss of autonomy. Knowledge about the trajectory of the disease or the trajectory of CKD is essential to effectively help patients and families succeed in ongoing efforts to care for the disease. The trajectory concept provides a way for healthcare professionals to think longitudinally and gain a fuller understanding of the nature of chronic diseases. The aim of this study was to analyze the illness trajectory of individuals with CKD undergoing hemodialysis treatment. This is a qualitative, descriptive research. The study setting was a nephrology service located in Belo Horizonte. The study participants were 25 people on hemodialysis, with a minimum of one year of treatment and over 18 years of age. Semi-structured interviews were used for data collection and, for analysis, the thematic Content Analysis technique. From the narratives, 3 trajectories of the disease were constructed. Each trajectory included eight phases of chronic disease according to the Corbin and Strauss model. The trajectories revealed that although the problems faced by the study participants were similar, the course of the disease was not the same for all of them, but they clearly exposed the weaknesses of the health services and professionals that make up the health care network. They are influenced by the context of each individual's life, in addition to the nature of the disease. They clearly highlighted the need to strengthen primary care as the gateway for users, in order to reduce vulnerabilities to CKD. The trajectories can facilitate the construction of care models that incorporate self-management approaches supported by health professionals, which could better meet the needs of those who live with this progressive disease over time. Knowledge about the trajectory of CKD proves to be a useful tool that has the potential to increase the adequacy of interventions designed for patients.